2002
DOI: 10.1111/j.1553-2712.2002.tb02175.x
|View full text |Cite
|
Sign up to set email alerts
|

Managing the Unique Size-related Issues of Pediatric Resuscitation: Reducing Cognitive Load with Resuscitation Aids

Abstract: A resuscitation is a complicated event that requires for its optimal outcome the effective completion of a distinct series of actions, some simple, some complex, most occurring simultaneously or in close proximity. In children, these actions are determined not only by the clinical situation, but also by a series of age and size factors particular to each child. Different tasks require different levels of cognitive load, or mental effort. Cognitive load describes the mental burden experienced by the decision ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 17 publications
1
63
1
1
Order By: Relevance
“…2) describing team member positions around the bed. Job aids may organize task priorities, standardize activities, prevent inadvertent oversights, allow faster and more thorough completion of tasks and reduce cognitive load [79][80][81]. They prevent leadership distractions or task drift, ensure a consistent structure to the resuscitation process and decrease team stress.…”
Section: Job Aids For Code Teamsmentioning
confidence: 99%
See 2 more Smart Citations
“…2) describing team member positions around the bed. Job aids may organize task priorities, standardize activities, prevent inadvertent oversights, allow faster and more thorough completion of tasks and reduce cognitive load [79][80][81]. They prevent leadership distractions or task drift, ensure a consistent structure to the resuscitation process and decrease team stress.…”
Section: Job Aids For Code Teamsmentioning
confidence: 99%
“…They prevent leadership distractions or task drift, ensure a consistent structure to the resuscitation process and decrease team stress. Job aids transfer resuscitation processes from deliberate cognitive processes to automatic reflexes [79,82,83].…”
Section: Job Aids For Code Teamsmentioning
confidence: 99%
See 1 more Smart Citation
“…Medication dosing, choice of equipment size, and determination of fluid volume for resuscitation all depend on the size of the child; thus, each must be determined or calculated in a high-risk environment by using high-level cognitive skills. Studies have shown that simple tools, such as a length-based tape that provides precalculated medication doses in colorcoded zones, 51 can reduce deviation from the recommended dose range (dosing error) by 25% in simulated resuscitation scenarios, compared with other traditional dosing references. 22 By providing a precalculated dose for a specific length or weight zone, the tool helps to simplify and standardize the complex task of pediatric resuscitation.…”
Section: Pediatric-specific Clinical Toolsmentioning
confidence: 99%
“…The weight of a child is critically important in pediatric dosing, and strategies have been developed to reduce cognitive errors associated with weighing. 22 Where direct weighing is necessary, it is clearly important to adopt one unit of weight only in the ED to remove any ambiguity.…”
Section: Case 13mentioning
confidence: 99%